2021
DOI: 10.3390/molecules26185537
|View full text |Cite
|
Sign up to set email alerts
|

Wine, Polyphenols, and Mediterranean Diets. What Else Is There to Say?

Abstract: A considerable amount of literature has been published claiming the cardiovascular benefits of moderate (red) wine drinking, which has been considered a distinguishing trait of the Mediterranean diet. Indeed, red wine contains relevant amounts of polyphenols, for which evidence of their biological activity and positive health effects are abundant; however, it is also well-known that alcohol, even at a low level of intake, may have severe consequences for health. Among others, it is directly related to a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 175 publications
(200 reference statements)
0
23
0
Order By: Relevance
“…The MedDiet’s health power lies on the foods’ heterogeneity, allowing the proper intake of key molecules, such as long-chain polyunsaturated fatty acids, fiber, antioxidant vitamins, carotenoids, and polyphenols. Of note, this is associated with beneficial effects on endothelial and cardiovascular function [ 81 ]. Estruch et al showed in prospective randomized controlled clinical trial enrolling high-risk patients for CVDs the decreased incidence of cardiovascular events in patients assigned to a Mediterranean Diet supplemented with extra-virgin olive oil or nuts when compared with those assigned to a reduced-fat diet [ 82 ].…”
Section: Evidence From the Clinical Trialsmentioning
confidence: 99%
“…The MedDiet’s health power lies on the foods’ heterogeneity, allowing the proper intake of key molecules, such as long-chain polyunsaturated fatty acids, fiber, antioxidant vitamins, carotenoids, and polyphenols. Of note, this is associated with beneficial effects on endothelial and cardiovascular function [ 81 ]. Estruch et al showed in prospective randomized controlled clinical trial enrolling high-risk patients for CVDs the decreased incidence of cardiovascular events in patients assigned to a Mediterranean Diet supplemented with extra-virgin olive oil or nuts when compared with those assigned to a reduced-fat diet [ 82 ].…”
Section: Evidence From the Clinical Trialsmentioning
confidence: 99%
“…RA is a natural antioxidant and anti-inflammatory polyphenol derived from many plants including M. officinalis . Polyphenols are characterized by numerous beneficial effects on the body, and RA, with its numerous properties, makes no exception, especially as a strong anti-inflammatory [ 34 , 35 , 36 , 37 ]. Indeed, RA was reported to exert anti-inflammatory effects against neuroinflammation in microglia cells [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Mediterranean diet, which includes significant plant polyphenols and wine consumption, has been associated with lower incidence of breast cancer [ 174 , 175 , 176 , 177 , 178 ]. Resveratrol has been identified as one of the protective bioactive molecules in this diet [ 179 ]. Additionally, resveratrol is thought to be the ingredient in wine responsible for the “French Paradox” effect, in which moderate wine consumption in French people is associated with low incidence of heart disease despite their high-fat diet [ 90 , 160 , 180 , 181 ].…”
Section: Phytoestrogens Targeting Bcscs and Their Mechanisms Of Actionmentioning
confidence: 99%